2021
DOI: 10.3233/jad-201031
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Receptor Polymorphisms with Amyloid-β Transporters Expression and Risk of Mild Cognitive Impairment in a Chilean Cohort

Abstract: Background: Amyloid-β peptide (Aβ) deposition in Alzheimer’s disease (AD) is due to an imbalance in its production/clearance rate. Aβ is transported across the blood-brain barrier by LRP1 and P-gp as efflux transporters and RAGE as influx transporter. Vitamin D deficit and polymorphisms of the vitamin D receptor (VDR) gene are associated with high prevalence of mild cognitive impairment (MCI) and AD. Further, vitamin D promotes the expression of LRP1 and P-gp in AD-animal model brains. Objective: To associate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Functionally, the neuroprotective effects of estrogens in neural cells against amyloid β-induced neurotoxicity are based on amyloid degradation or other molecular mechanisms (Yagyu et al, 2002;Marin et al, 2003;Quintanilla et al, 2005;Amtul et al, 2010). A cohort study indicated female patients with poor cognitive performance is associated with insufficient levels of VitD, whereas no such association was observed in male patients (Arévalo et al, 2021). The possible hypothesis is that body fat in women is greater than in men, and in this way circulating vitamin D can be stored in adipose tissue and, given its lipophilic characteristics, would be less available in plasma (Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functionally, the neuroprotective effects of estrogens in neural cells against amyloid β-induced neurotoxicity are based on amyloid degradation or other molecular mechanisms (Yagyu et al, 2002;Marin et al, 2003;Quintanilla et al, 2005;Amtul et al, 2010). A cohort study indicated female patients with poor cognitive performance is associated with insufficient levels of VitD, whereas no such association was observed in male patients (Arévalo et al, 2021). The possible hypothesis is that body fat in women is greater than in men, and in this way circulating vitamin D can be stored in adipose tissue and, given its lipophilic characteristics, would be less available in plasma (Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some underlying genes, such as CYP27A1 and CYP27B1, could affect the function of BsmI, ApaI, and TaqI (Cheng et al, 2004;Uitterlinden et al, 2004). The ApaI genotype was found to affects the mRNA expression of target gene, including P-gp, LRP1, and RAGE, facilitating brain Aß aggregation (Arévalo et al, 2021). The Apa1 and Taq1 polymorphisms have potential interaction with interleukin-10 (IL-10) SNP, suggesting that the candidate gene may have superimposed effects with the Apa1 or Taq1 in the AD progression (Lehmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Castillo-Mendieta et al [18] report the potential of plasma biomarkers of neuropathological signs of AD as a cost-effective approach to identifying individuals at risk for AD in a sample of Mexican AD patients. Arévalo et al [19] propose a role for vitamin D receptor polymorphisms in MCI and AD in a Chilean sample and include studies in peripheral blood mononuclear cells. Ayala-Gross et al [20] report the results of cross-sectional analyses that suggest that chronic dysregulation of cortisol secretion may contribute to cognitive impairment using data from PAHO/WHO agencies.…”
Section: Introductionmentioning
confidence: 99%